A Self‐Forming Composite Electrolyte for Solid‐State Sodium Battery with Ultralong Cycle Life. Issue 4 (31st October 2016) - Zhang, Zhizhen; Zhang, Qinghua; Shi, Jinan; Chu, Yong S.; Yu, Xiqian; Xu, Kaiqi; Ge, Mingyuan; Yan, Hanfei; Li, Wenjun; Gu, Lin; Hu, Yong‐Sheng; Li, Hong; et al.
Abstract : Replacing organic liquid electrolyte with inorganic solid electrolytes (SE) can potentially address the inherent safety problems in conventional rechargeable batteries. However, solid‐state batteries (SSBs) have been plagued by the relatively low ionic conductivity of SEs and large charge‐transfer resistance between electrode and SE. Here, a new design strategy is reported for improving the ionic conductivity of SE by self‐forming a composite material. An optimized Na + ion conducting composite electrolyte derived from the Na1+ n Zr2 Si n P3− n O12 NASICON (Na Super Ionic Conductor) structure is successfully synthesized, yielding ultrahigh ionic conductivity of 3.4 mS cm −1 at 25 °C and 14 mS cm −1 at 80 °C. On the other hand, in order to enhance the charge‐transfer rate at the electrode/electrolyte interface, an interface modification strategy is demonstrated by utilization of a small amount of nonflammable and nonvolatile ionic liquid (IL) at the cathode side in SSBs. The IL acts as a wetting agent, enabling a favorable interface kinetic in SSBs. The Na3 V2 (PO4 )3 /IL/SE/Na SSB exhibits excellent cycle performance and rate capability. A specific capacity of ≈90 mA h g −1 is maintained after 10 000 cycles without capacity decay under 10 C rate at room temperature. This provides a new perspective to design fast ion conductors and fabricate long life SSBs. Abstract : A room‐temperature ionic conductivity of 3.4 mS cm −1 is obtained in a self‐forming composite solid electrolyte. On the other hand, an interface modification strategy that involves adding a small amount ionic liquid at the cathode side is proposed. The combination of this composite electrolyte and ionic liquid allows solid‐state battery to exhibit excellent rate capability and cycling performance at room temperature.